Prevalence and Risk Factors of Gallbladder Stones and Polyps in Liaoning, China - Xinhe Zhang (Frontiers in Medicine, 2022)
ObjectiveTo investigate the incidence and risk factors of gallbladder stones and polyps in individuals undergoing physical examinations in Liaoning province, China.MethodsThis is a retrospective study of adults who underwent routine health examinations at Xikang Medical Center in Liaoning Province (Shenyang, Dandong, and Dalian) from 01/2016 to 12/2020. The routine health examination included anthropometry, blood tests, and liver ultrasound. Based on liver ultrasound results, patients were grouped into those with gallbladder stones, those with gallbladder polyps, those with both stones and polyps, and those with neither.ResultsOf the 284,129 included subjects, 6,537 (2.30%) were diagnosed with gallbladder stones, and 18,873 (6.64%) were diagnosed with gallbladder polyps. The overall prevalence in Liaoning province increased each year, peaking in 2020. The prevalence of gallbladder stones was higher among females than males (2.39% vs. 2.23%, respectively), while the prevalence of gallbladder polyps was higher among males. The gallbladder polyp group had higher BMI, FBG, SBP, DBP, TG, TC, LDL-C, HDL-C, AST, ALP, GGT, BUN, Scr, SUA. Except for HDL-C, all factors were also higher in the gallbladder stone group. Patients with fatty liver had a higher prevalence of gallbladder stones and polyps than participants without fatty liver.ConclusionThe prevalence of gallbladder stones and polyps in Liaoning varies by sex, economic status of the city of residence, BMI, and metabolic indicators.